Evaluation of antimicrobial prescription pattern in Neonatal Intensive care unit of tertiary care teaching hospital - Sanjio Borade; Sarang Ghodki; Ashok Bhore; Satish Tiwari; Shreepad Jahagirdar; Kishor Bansod (International Journal of Medical Research and Review, 2014)
Introduction: Neonates admitted in Neonatal Intensive Care Units (NICU) have high morbidity and mortality with very subtle and subjective clinical signs. Hence/so Anti Microbial Agents (AMAs), being/become mainstay drugs, are often used empirically and irrationally.Method: This is cross- sectional study over the period of six months from October 2012 to March 2013. Clinical, hematologic, laboratory, microbiologic and therapeutic data were collected, analyzed and evaluated from the case papers of NICU. Rational use in our study means appropriate dose, duration, frequency and route of administration appropriate to clinical conditions.Result: Of 118 neonates, 66 (56%) were treated rationally. Approximately 60 % times appropriate dose and frequency of drugs were given. Cefotaxime was most commonly prescribed AMA for neonates (73.73 %). In our study low birth weight neonates have received more antibiotics in comparison with term babies.Conclusion: AMA prescription policy be formulated and displayed in NICU to promote rational prescription.